Application and testing of a framework for characterizing the quality of scientific reasoning in chemistry students' writing on ocean acidification. Issue 3 (1st April 2019) - Moon, Alena; Moeller, Robert; Gere, Anne Ruggles; Shultz, Ginger V.
Abstract : Science educators recognize the need to teach scientific ways of knowing and reasoning in addition to scientific knowledge. However, characterizing and assessing scientific ways of knowing and reasoning is challenging. Writing-to-learn offers one way of eliciting and supporting students' reasoning; further, writing serves to externalize and make traceable students' reasoning. For this reason, it is a useful formative assessment of scientific reasoning. The utility hinges on researchers' ability to understand what students can do and think from their writing. Given the challenges in assessing students' writing, this research offers an adapted framework for assessing students' scientific reasoning evident in writing. This work will introduce an adapted framework and show an application to general chemistry students' argumentative writing about ocean acidification. We provide evidence that this framework can be used to validly estimate the quality of students' reasoning. We argue that this framework offers some affordances that overcome challenges reported in the literature. It serves to define scientific reasoning in a domain-general way by breaking it down into its components, but in a way that can produce a composite score that tells us about how students reason using chemistry content. Further, the framework provides a way to characterize the scientific accuracy of students' reasoning that can inform instructors' treatment of alternative conceptions.